(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2020)
Human rights have progressed from the general to the particular, in this context the rights of women are enshrined, which main instrument is the Convention on the Elimination of All Forms of Discrimination against Women, this instrument condemns the different forms of discrimination and pursues as a fundamental objective equality between men and women; its enforcement and control body, the Committee, deploys a series of mechanisms and must face a variety of challenges to advance in the real application of the rights and principles of the Convention.